Parallel programming with VPE: a case study of an integrated visual programming environment - Turner, S.J.; Wentong Cai; Hung-Khoon Tan (High-Performance Computing on the Information Superhighway, 1997)
With the increased complexity of applications, parallel computing has proved to be an alternative to supercomputing in solving large problems. However developing parallel applications is more difficult compared to sequential programming. Visual technologies can be employed to aid the multi-dimensional tasks of parallel programming. This paper presents a case study of the use of an integrated visual programming environment in creating parallel applications. Techniques for the hierarchical construction of parallel programs are presented, together with an evaluation of the performance of the generated code for a matrix multiplication application.